Embracing Multimodality To Teach EFL Students: English Course Teachers’ Perspectives - Septianing Putri, Yulinda; Setyaningsih, Endang; Adi Putra, Kristian (CV. Inara, 2024)
This article explores the Indonesian English course teachers’ perception on the use of multimodal teaching resources to enhance the learning experience of English as a Foreign Language (EFL) students. Multimodal resources, which integrate various modes of communication such as text, audio, visuals, and interactive elements, are designed to cater to different learning styles and preferences. The study highlights the benefits of multimodality, including increased student engagement, improved comprehension, etc. This study used qualitative research methodology to gain the teachers’ perception of multimodal teaching resources implementation. The participants were experienced English course teachers over three years teaching in the Ruang Guru platform. Furthermore, the researcher used semi-structured interviews to collect the data. Despite the advantages, the article also discusses the challenges associated with implementing multimodal resources, such as technological barriers and the time required for resource creation. The findings showed that teachers really understand the term of multimodal teaching resources before conducting it in their teaching and learning process. It found that the utilization of multimodal teaching resources has several advantages for teachers to support their teaching, however in preparing and using these multimodal resources, teachers encounter several obstacles and difficulties. By embracing multimodality and addressing these challenges, educators can create a more inclusive and effective learning environment for EFL students.